Adaptive Ability of Children Aged 5-6 Years as a Component of Social-Emotional Development - Ratna Nila Puspitasari (Kumara Cendekia, 2026)
Social-emotional development is a fundamental aspect of early childhood development, this is because social-emotional development can support children's ability to regulate emotions, and social interactions, as well as adapt to the demands of the environment. One of the important components of socio-emotional development is adaptability, which refers to the ability of children to adapt their emotional responses and behaviors in accordance with social rules, routines, and situational changes. This study aims to describe adaptability as a component of social-emotional development in early childhood, with a focus on children aged 5-6 years. This study used a quantitative descriptive design involving 34 children aged 5-6 years. Data were collected using observational instruments that measured adaptability across four indicators. The data were analyzed using descriptive statistics, including mean scores and standard deviations, to describe the child's level of adaptability. The results of the study show that children's adaptability is generally in the medium to high category. Two indicators showed high average scores, indicating that most children were able to demonstrate adaptive behavior consistently in structured classroom situations. Two indicators are categorized at a moderate level, indicating that adaptability is still developing consistently. These findings illustrate that the development of adaptive abilities in early childhood develops gradually. In conclusion, adaptability among children aged 5-6 years has emerged and its  development is increasingly stable.